Trace metals' contamination in water and soils in the vicinity of a small–medium waste electrical and electronic equipment recycling plant. Issue 3 (3rd September 2019) - Tzoraki, Ourania; Zkeri, Eirini; Lasithiotakis, Michael; Sinioros, Panagiotis
Abstract: An e‐waste recycling plant's ecological burden is correlated to soil and water, inside and outside the plant with inductively coupled plasma‐mass spectrometry. Correlation between heavy metal concentrations was calculated with Spearman's rho correlation coefficients. Ecological risk was assessed with ecological risk indexes (RIs) such as Hakanson's ecological RI, Geoaccumulation index, and enrichment factors. Heavy metals in water comply with drinking water criteria, except Pb in one water sample W2. Concentrations of Pb, Cr, Ni, Cu, Mn, and Zn were higher in the rainwater collection tank (43.50, 10.90, 18.87, 81.17, 177.99, and 330.17 μg/L) than the surficial water inside (8.93, 1.27, 4.97, 17.0, 91.87, and 72.97 μg/L) and outside the plant (4.18, 1.28, 1.60, 10.35, 26.21, and 12.10 μg/L). In most water samples, As, Li, Mg, Ca, Na, Ba, Si, Sr, U, and V concentrations were at similar levels and are not influenced by the company's activities except the rainwater tank. Water samples correlation results showed statistically significant positive correlation between (a) Al, Fe, Pb, Ce, Co, La, Nd, Sm, Y and (b) Cu and Mn—an anthropogenic influence related with e‐waste. Ecological RIs for soils showed low to moderate pollution. The most enriched soil samples in Cu, Pb, Zn, Cd, and Hg were two samples west of the plant, and another two east of the plant. Pb comes from cathode ray tubes. A pH‐edge desorption study concluded that the cation exchange processes with clays and the strong sorption affinity of Fe oxides keep metals bound to the soil matrix.